Individual and contextual factors of nulliparas' levels of depression, anxiety and fear of childbirth in the last trimester of pregnancy: intimate partner attachment a key factor? - Prelog Polona Rus; Makovec Maja Rus; Šimic Marijana Vidmar; Sršen Tanja Premru; Perat Mitja (Sciendo, 2019)
Depression, anxiety and fear of childbirth have numerous consequences for women and their developing offspring. Insecure attachment in close adult relationships is considered to be a risk factor for depressive symptoms. This study aims to gain further insight into the risk factors for depressive and anxiety symptoms in nulliparous women during the third trimester of pregnancy regarding the main contextual relations, with an emphasis on partner attachment.